Answer:
(5x² + 3)(2x - 7)
Step-by-step explanation:
First, we need to group the first two terms and the last two terms, so:
10x³ - 35x² + 6x - 21
(10x³ - 35x²) + (6x - 21)
We can write each term as follows:
10x³ = 5x²(2x)
35x² = 5x²(7)
6x = 3(2x)
21 = 3(7)
So, we can factor 5x² from the first term (10x³ - 35x²) and we can factor 3 from the second term (6x - 21). Then, we get:
5x²(2x - 7) + 3(2x - 7)
Now, we need to factor (2x -7), so:
(5x² + 3)(2x - 7)
So, the factorization of the polynomial 10x³ - 35x² + 6x - 21 is:
(5x² + 3)(2x - 7)